Respuesta :
Answer: Division (choice B)
====================================================
If you add the two polynomials, you get
(6x^2-2)+(6x^2+2) = 12x^2
which is another polynomial.
We can rule out choice A.
----------------
If you subtract the polynomials, the same kind of story happens (but you'll get a different polynomial)
(6x^2-2)-(6x^2+2) = -4
The term -4 is a polynomial of degree 0.
We can rule out choice D.
-----------------
If you multiply the two polynomials, then you get another polynomial. Use the FOIL rule
(6x^2-2)(6x+2) = 36x^2 + 12x - 12x - 4 = 36x^2 - 4
or you could use the difference of squares rule to help expand
(6x^2-2)(6x+2) = (6x)^2 - (2)^2 = 36x^2 - 4
or you could use the box method (see Figure 1 in the attached images below)
Whichever method you use, the result is 36x^2 - 4 which is another polynomial.
We can rule out choice C. The only thing left is choice B.
-------------------
When dividing two polynomials, it is not always guaranteed to get another polynomial as a result. Use polynomial long division to calculate (6x^2-2)/(6x^2+2) and you'll get what you see in Figure 2 below. Figure 3 shows the long division table for (6x^2+2)/(6x^2-2). Both figures 2 and 3 show a nonzero remainder. The nonzero remainder means the result is not a polynomial.
![Ver imagen jimthompson5910](https://us-static.z-dn.net/files/d9c/f559a7dec533cc19c181b12be1d5f90e.png)
![Ver imagen jimthompson5910](https://us-static.z-dn.net/files/d22/49e29575421ff29268ae0e7b968fbab6.png)
![Ver imagen jimthompson5910](https://us-static.z-dn.net/files/da9/cfea7422f00789a9928328171a51499d.png)